Feasibility of a pragmatic randomized adaptive clinical trial to evaluate a brief negotiational interview for harmful and hazardous alcohol use in Moshi, Tanzania. - Catherine A Staton; Kaitlyn Friedman; Ashley J Phillips; Mary Catherine Minnig; Francis M Sakita; Kennedy M Ngowi; Brian Suffoletto; Jon Mark Hirshon; Monica Swahn; Blandina T Mmbaga; Joao Ricardo Nickenig Vissoci (PLoS ONE, 2023)
Introduction Low-resourced settings often lack personnel and infrastructure for alcohol use disorder treatment. We culturally adapted a Brief Negotiational Interview (BNI) for Emergency Department injury patients, the "Punguza Pombe Kwa Afya Yako (PPKAY)" ("Reduce Alcohol For Your Health") in Tanzania. This study aimed to evaluate the feasibility of a pragmatic randomized adaptive controlled trial of the PPKAY intervention. Materials and methods This feasibility trial piloted a single-blind, parallel, adaptive, and multi-stage, block-randomized controlled trial, which will subsequently be used to determine the most effective intervention, with or without text message booster, to reduce alcohol use among injury patients. We reported our feasibility pilot study using the Reach, Effectiveness, Adoption, Implementation, Maintenance (RE-AIM) framework, with recruitment and retention rates being our primary and secondary outcomes. We enrolled adult patients seeking care for an acute injury at the Kilimanjaro Christian Medical Center in Tanzania if they (1) exhibited an Alcohol Use Disorder Identification Test (AUDIT) ≥8, (2) disclosed alcohol use prior to injury, or (3) had a breathalyzer ≥0.0 on arrival. Intervention arms were usual care (UC), PPKAY, PPKAY with standard text booster, or a PPKAY with a personalized text booster. Results Overall, 181 patients were screened and 75 enrolled with 80% 6-week, 82.7% 3-month and 84% 6-month follow-up rates showing appropriate Reach and retention. Adoption measures showed an overwhelmingly positive patient acceptance with 100% of patients perceiving a positive impact on their behavior. The Implementation and trial processes were performed with high rates of PPKAY fidelity (76%) and SMS delivery (74%). Intervention nurses believed Maintenance and sustainability of this 30-minute, low-cost intervention and adaptive clinical trial were feasible. Conclusions Our intervention and trial design are feasible and acceptable, have evidence of good fidelity, and did not show problematic deviations in protocol. Results suggest support for undertaking a full trial to evaluate the effectiveness of the PPKAY, a nurse-driven BNI in a low-income country. Trial registration Trial registration number NCT02828267. https://classic.clinicaltrials.gov/ct2/show/NCT02828267.